The Origins of the Institute for the History and Philosophy of Science and Technology - Enros, Philip (Scientia Canadensis, 2016)
An effort to establish programs of study in the history of science took place at the University of Toronto in the 1960s. Initial discussions began in 1963. Four years later, the Institute for the History and Philosophy of Science and Technology was created. By the end of 1969 the Institute was enrolling students in new MA and PhD programs. This activity involved the interaction of the newly emerging discipline of the history of science, the practices of the University, and the perspectives of Toronto’s faculty. The story of its origins adds to our understanding of how the discipline of the history of science was institutionalized in the 1960s, as well as how new programs were formed at that time at the University of Toronto.